SOIL PROPERTIES UNDER SIX COCONUT CROPPING SYSTEMS - DOAH DEKOK TAR1GANS (Jurnal Penelitian Tanaman Industri, 1999)
Thee wee a number of factors causing diffeences in coconut growth and soil properties under ield condition. To cope with the existing vaiation fanning system in relation to soil properties, six coconut farming systems with four species of perenial crops as inter- crop(s) namely banana, papaya, coffee and pineapple wee conducted understudy. The objectives of the study were to study soil chemical and physical properties and nutrient element content in the coconut leave under various coconut cropping systems. Six coconut farming system as used for the study namely (I) coconut (control), (2) coconut + pineapple, (3) coconut + coffee, (4) coconut + papaya + pineapple, (5) coconut + banana + coffee, and (6) coconut + banana ♦ papaya + coffee + pineapple. Total area for each system is 0.5 ha. Data on leaf analysis parameters, soil chemical poperties and soil physical parameters, wee statistically analyzed in randomized complete block design (RCBD) with three replications. The organic matter, pH and cation exchange capacity of the soils did not differ significantly with cropping pattern, although intensively cropped farm tended to have higher organic matter and cation exchange capacity values. Nitrogen, phosphorus and potassium wee also significantly higher in intercropped farms but calcium and magnesium did not vary signiicantly. While moistue content, water holding capacity, bulk density of the soil did not show significantly difference with cropping patterns. Leaf nitrogen and calcium incease while potassium deceased with intensity of cropping. Phosphorus and magnesium showed no diinite trend. Leaf nitrogen, phosphorus and calcium were all positively correlated with soil nitrogen but soil phosphorus was weakly correlated with all nutrient element in the leaf. The exchangeable potassium in the topsoil was positively and insigniicantly with nitrogen, potassium and calcium but negatively insignificantly with phosphorus and magnesium concentration in coconut leaf. While the exchangeable calcium in the subsoil was significantly and positively correlated with nitrogen in the leaf but negatively corelated with potassium.